Hoya (Apocynaceae: Asclepiadoideae) diversity in Gunung Gede Pangrango National Park, West Java, Indonesia. - Rahayu, Sri (Research Center for Biology, 2012)
A survey on the diversity of Hoya (Apocynaceae: Asclepiadoideae) species was conducted in Gunung Gede Pangrango National Park at different altitudes in four locations (Cibodas, Bodogol, Situgunung, and Selabintana). Ten Hoya species were found at elevations between 650 and 1500 m asl. Of these, two species were only found at elevations above 1000 m asl, while the other eight grow well below 1000 m asl.ÃÂ The inventory encountered Hoya imperialis Lindley and H. micrantha Wight ex Hook.f. as new records for Java.ÃÂ The highest diversity was found at the Bodogol Research Station. It shows that the genus is most diverse at relatively low altitudes.